Taming of the few : the unequal distribution of greenhouse gas emissions from personal travel in the UK - Brand, C; Boardman, B (Elsevier, 2008)
Greenhouse gas emissions from personal transport have risen steadily in the UK. Yet, surprisingly little is known about who exactly is contributing to the problem and the extent to which different groups of the population will be affected by any policy responses. This paper describes an innovative methodology and evaluation tool for profiling annual greenhouse gas emissions from personal travel across all modes of travel. A case study application of the methodology involving a major survey of UK residents provides an improved understanding of the extent to which individual and household travel activity patterns, choice of transport mode, geographical location, socio-economic and other factors impact on greenhouse gas emissions. Air and car travel dominate overall emissions. Conversely, land-based public transport accounts for a very small proportion of emissions on average. There is a highly unequal distribution of emissions amongst the population, independent of the mode of travel, location and unit of analysis. The top 10% of emitters are responsible for 43% of emissions and the bottom 10% for only 1%. Income, economic activity, age, household structure and car availability significantly influence emissions levels. Key policy implications of the results are discussed. The paper concludes by suggesting potential applications of the methodology and evaluation tool.